Integrated multi-omics profiling reveals the role of the DNA methylation landscape in shaping biological heterogeneity and clinical behaviour of metastatic melanoma - Andrea Anichini; Francesca P. Caruso; Vincenzo Lagano; Teresa M. R. Noviello; Rossella Tufano; Gabriella Nicolini; Alessandra Molla; Ilaria Bersani; Francesco Sgambelluri; Alessia Covre; Maria F. Lofiego; Sandra Coral; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background We developed an integrated multi-omics analysis in metastatic melanoma (MM) cohorts to associate DNA methylation profiles with tumor progression, survival, response to adjuvant immunotherapy, structure of the tumor immune microenvironment and transcriptional programs of immunity and melanoma differentiation. Methods Lesions (n = 191) from a fully annotated, retrospective cohort of 165 AJCC 8th Stage III and IV melanoma patients (EPICA cohort) were characterized by reduced representation bisulfite sequencing, RNA sequencing, whole exome sequencing, quantitative immunohistochemistry and multiplex immunofluorescence analysis. The TCGA melanoma datasets were used for validation. Pre-therapy lesions (n = 28) from a cohort of MM patients treated with adjuvant immune checkpoint blockade were characterized for the DNA methylation profile. Impact of a DNMT inhibitor on DNA methylation and transcriptomic profiles of melanoma cell lines was investigated by EPIC arrays and Clariom S arrays. Results Four tumor subsets (i.e. DEMethylated, LOW, INTermediate and CIMP) with progressively increasing levels of DNA methylation were identified in EPICA, TCGA MM and TCGA primary melanoma cohorts. EPICA patients with LOW methylation tumors exhibited a significantly longer survival and a lower progression rate to more advanced AJCC stages, compared to patients with CIMP tumors. In an adjuvant immune checkpoint blockade cohort, patients with DEM/LOW pre-therapy lesions showed significantly longer relapse-free survival compared to those with INT/CIMP lesions. RNA-seq data analysis revealed that LOW and CIMP EPICA tumors showed opposite activation of master molecules influencing prognostic target genes, and differential expression of immunotherapy response and melanoma differentiation signatures. Compared to CIMP tumors, LOW lesions showed enrichment for CD8+ TCF-1+ PD-1+ TIM-3− pre-exhausted and CD8+ TCF-1− PD-1+ TIM-3+ exhausted T cells, more frequent retention of HLA Class I antigens and a de-differentiated melanoma phenotype. The differentiation and immune-related transcriptional features associated with LOW vs CIMP lesions were tumor-intrinsic programs retained in-vitro by melanoma cell lines. Consistently, treatment of differentiated melanoma cell lines with a DNMT inhibitor induced global DNA de-methylation, promoted de-differentiation and upregulated viral mimicry and IFNG predictive signatures of immunotherapy response. Conclusions These results reveal the biological, prognostic and therapeutic relevance of DNA methylation classes in MM and support methylome targeting strategies for precision immunotherapy.